Cystic with mural nodule: Unusual radiological presentation of supratentorial anaplastic ependymoma - Borkar, Sachin A. (Medknow Publications & Media Pvt Ltd, 2012)
Supratentorial anaplastic ependymoma is an uncommon tumor which can rarely present as a cyst with mural nodule on imaging. Authors present this unusual radiological appearance of supratentorial extraventricular anaplastic ependymoma in a 9-year-old boy.